The Study of EFL Learnersʹ Perception of Using E-learning, Self-Regulation and Constructivism in English Classrooms: Teachers, Intermediate and Advanced Learners' Attitude - Marzie Faridi; Siros Izadpanah (National Research University Higher School of Economics, 2024)
Introduction: Effective ways of acquiring a second language in an educational context undergo development in teaching and learning through e-learning, self-regulated learning, and constructivism methods of learning that would be practical and useful for EFL learners.     Purpose: To investigate the impact of self-regulated learning, constructivism, and e-learning on English language learning and the attitudes of learners toward them. Method: The study employs a quantitative research method involving 360 intermediate and advanced EFL learners and 34 teachers. Data were collected over a six-week period in Zanjan English language institutes using the questionnaires. The one-sample T-test compared the means, while ANOVA assessed significant differences among the variable means of E-learning, self-regulation, and constructivism in the study groups. Post-hoc LSD tests were used to compare the means of groups two by two. Results: The results showed that the participants displayed positive attitudes toward using e-learning, self-regulation, and constructivism in acquiring a second language. Qualitative data analysis revealed EFL learners' autonomy in learning and the potential influence of teachers in shaping learners' attitudes.    Conclusion: This study highlights the importance of considering learners' attitudes and autonomy in designing effective language learning environments. Understanding the learners' perspectives can aid educators in adopting innovative and learner-centered approaches, leading to enhanced language learning outcomes.